Risk for depression and psychological well-being in german national and state team athletes - Associations with age, gender, and performance level - Belz, J.; Kleinert, J.; Ohlert, J.; Rau, T.; Allroggen, M. (Journal of Clinical Sport Psychology, 2018)
Adolescence is a vulnerable period for the development of depression. Research on depression in athletes including adolescent athletes, however, is scarce. The purpose of the present study was to assess the risk for depression depending on the athletes` age, gender, and performance level. Data were collected from 1,799 German national and state team athletes. The PHQ-2 and the WHO-5 were administered to assess the athletes` risk for depression and current state of psychological well-being. Overall, 13% of the athletes were screened positive for depression and 10% for impaired well-being. Adolescents, females and athletes of junior national teams showed a higher risk for depression and/or lower well-being than other subgroups. The finding that adolescent athletes are more vulnerable to suffer from depressive symptoms than adult athletes mirrors finding in the general population. Screening tools for depression should be followed up by clinical expert interviews to provide an external criterion for the obtained results.